Regional coronary endothelial dysfunction is related to the degree of local epicardial fat in people with HIV. (November 2018) - Iantorno, Micaela; Soleimanifard, Sahar; Schär, Michael; Brown, Todd T.; Bonanno, Gabriele; Barditch-Crovo, Patricia; Mathews, Lena; Lai, Shenghan; Gerstenblith, Gary; Weiss, Robert G.; Hays, Allison G.
Abstract: Background and aims: Coronary artery disease (CAD) is now an important cause of premature death in people with HIV but the causes of accelerated CAD are poorly understood. Epicardial adipose tissue (EAT) is metabolically-active and thought to contribute to CAD development. We tested the hypothesis that abnormal coronary endothelial function (CEF), an early marker and mediator of atherosclerosis, is related to the amount of local pericoronary EAT in HIV. Methods: We studied 36 participants with HIV and no CAD (HIV+ CAD-), 15 participants with HIV and known CAD (HIV+ CAD+), and 14 age-matched, healthy participants without HIV (HIV-CAD-). To measure CEF, coronary MRI was performed before and during isometric handgrip exercise (IHE), an endothelial-dependent stressor. EAT was measured with MRI at the same imaging plane as CEF. Results: CEF was significantly depressed, as measured by IHE-induced % coronary cross sectional area (CSA) change, in HIV+ CAD- and HIV+ CAD+ as compared to HIV-CAD-participants ( p <0.0001). EAT thickness was significantly greater in HIV+ CAD- and HIV+ CAD+ participants as compared to HIV-CAD-participants ( p =0.001). There was a significant inverse relationship between CEF and local EAT thickness and area (R = −0.48 and R = −0.51 respectively, p <0.0001 for both) among participants with HIV even after adjustment for cardiovascular risk factors. In participants with multiple CEF measures, CEF was lower in segments with higher EAT, other factors being equivalent. Conclusions: There is a significant relationship between increased metabolically-active EAT and depressed local CEF in people with HIV, consistent with the hypothesis that increased epicardial fat contributes to accelerated CAD in persons with HIV. Highlights: Coronary artery disease (CAD) is an important cause of death in people with HIV but the causes are poorly understood. Epicardial adipose tissue (EAT) is metabolically-active and thought to contribute to CAD development. Coronary endothelial dysfunction, an early mediator of CAD, is related to the amount of local pericoronary EAT in HIV. These findings suggest that increased epicardial fat may contribute to accelerated CAD in people with HIV.